Book Review on "Alsho'ara al-Mohadathoon - sayyed reza mirahmadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The discussion of modernism and its pioneers is not new and goes back to the origins of modernism and the mingling of Arabic culture with other cultures that affected literary criticism in the works of many authors including Hajiz, Qodamah Ben Jafar, Ibne Qotaibah, Abolfaraj Isfahani and many others.This has been analytically discussed by Hasan Darvish in his work "Alsho'ara al-Mohadathoon". He has shown modernism in different aspects of the works of poets. He has also compiled an excellent list of modernists and looked at different aspects of their poetry including the new language of poetry, novelty, structure, imagery, musicality, and intention. The voice of the author is clearly heard in this work through which he discusses different views and confirms or disconfirms them with acceptable evidence, and wherever possible expresses his own independent views on modernism